Design of a Compact Planar Rectenna for Wireless Power Transfer in the ISM Band - Fang Zhang; Xin Liu; Fan-Yi Meng; Qun Wu; Jong-Chul Lee; Jin-Feng Xu; Cong Wang; Nam-Young Kim (International Journal of Antennas and Propagation)
This paper presents a compact planar rectenna with high conversion efficiency in the ISM band. The proposed rectenna is developed by the decomposing of a planar rectenna topology into two functional parts and then recombining the two parts into a new topology to make the rectenna size reduction. The operation mechanism of the antenna and rectifying circuit in the proposed novel topology is explained and the design methodology is presented in detail. The proposed topology not only reduces the rectenna design cycle time but also leads to easy realization at the required frequency ranges with a very low cost. For validation, a 2.45 GHz rectenna system is designed and measured to show their microwave performances.